Looking beyond the fed: Do central banks cause information effects? - Christopher D. Cotton (Federal Reserve Bank of Boston, 2022)
The importance of central bank information effects is the subject of an ongoing debate. Most work in this area focuses on the limited number of monetary policy events at the Federal Reserve. I assess the degree to which nine other central banks cause information effects. This analysis yields a much larger panel of primarily novel events. Following a surprise monetary tightening, economic forecasts improve in line with information effects. However, I find this outcome is driven by the predictability of monetary policy surprises and not information effects. My results support the view that central bank information effects may be overstated.
Keywords: E43; E52; E58; 330; information effect; forecasts; monetary policy surprise; central bank